THE MANAGEMENT OF ENDO-PERIO LESION WITH FURCATION INVOLVEMENT: CASE REPORT - Ashari, Verawati; syahputra, armia; effendi, erdi; zovi, zovi; Budi, Budi; putra, wiriananta; Farahanny, Wandania; prasetia, widi prasetia (Universitas Baiturrahmah, 2024)
Introduction: Teeth with furcation involvement lesions present a significant challenge for clinicians regarding treatment options. Various methods can be employed to restore mutilated teeth for a longer period of function, including resective surgery (hemisection, bicuspidization and root amputation/root resection). Case and Management: This case series presents clinical and radiographic data collected from two patients who were referred to the dental and oral hospital at the University of Sumatera Utara. The patients were examined and treated by a dental conservation resident, who diagnosed a periodontal case in the patient with a chief complaint of pain and swelling associated with class II and III furcation involvement, as well as endo perio lesions on the radiograph of the first lower left and right mandibular molars. The class II and III furcation was complicated with endodontic involvement. Patients were provided with endodontic treatment in conjunction with the initial stage of periodontal treatment, which includes dental health education, root scaling and debridement. Following three months of endodontic treatment, resective surgery, including hemisection and bicuspidation, were performed. Radiographic analysis revealed that the teeth exhibited satisfactory regeneration following resective surgery, with the teeth becoming the supporting teeth for the fixed denture. Conclusion: It is not always necessary to extract teeth with conditions involving furcation. However, a multidisciplinary approach is essential to ensure effective treatment of the lesion.